2000
DOI: 10.4049/jimmunol.164.6.3200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Rejection and Immune Memory Elicited by Locally Released LEC Chemokine Are Associated with an Impressive Recruitment of APCs, Lymphocytes, and Granulocytes

Abstract: The human β chemokine known as LEC (also called NCC-4, HCC-4, or LMC) displays chemotactic activity for monocytes and dendritic cells. The possibility that its local presence increases tumor immunogenicity is addressed in this paper. TSA parental cells (TSA-pc) are poorly immunogenic adenocarcinoma cells that grow progressively, kill both nu/nu and syngeneic BALB/c mice, and give rise to lung metastases. TSA cells engineered to release LEC (TSA-LEC) are still able to grow in nu/nu mice, but are promptly reject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 24 publications
2
63
0
Order By: Relevance
“…The antibody titer is expressed as serum binding potential ϫ 10 Ϫ3 /mL, calculated as previously described in detail. 11 Complement-dependent cytotoxicity. DT6606 or K8484 cells were seeded in a 96-well plate (5 ϫ 10 3 /well) in Dulbecco's modified Eagle medium/1% fetal bovine serum overnight for adhesion.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…The antibody titer is expressed as serum binding potential ϫ 10 Ϫ3 /mL, calculated as previously described in detail. 11 Complement-dependent cytotoxicity. DT6606 or K8484 cells were seeded in a 96-well plate (5 ϫ 10 3 /well) in Dulbecco's modified Eagle medium/1% fetal bovine serum overnight for adhesion.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Interleukin-13 receptor (IL-13R) overexpression profoundly inhibited MDA-MB-231 tumor in athymic nude mice, but no difference in vitro growth was found between the transfected cells and mock cells (Kawakami et al, 2001). These phenomenon also exist for many chemokines, such as CCL16 (liverexpressed chemokine, LEC) (Giovarelli et al, 2000) and CCL19 (EBI1-ligand chemokine, ELC) (Braun et al, 2000).…”
Section: Inhibition Of Breast Cancer Growth and Metastasis By Darcmentioning
confidence: 99%
“…CCL16 was shown to be induced in monocytes by IL-10 (3) and chemotactic for monocytes and lymphocytes (3,4). In addition, this chemokine was shown to have a potent myelosuppressive activity comparable to that of MIP-1␣/CCL3 (4) and to induce tumor rejection (7). Previously, we have shown that CCL16 is a low-affinity functional ligand for CCR1, CCR2, and CCR5 (6).…”
Section: Liver-expressedmentioning
confidence: 99%
“…To examine whether any chemokines act as an agonist for the histamine receptors, we performed calcium mobilization assays using murine L1.2 pre-B cells stably expressing H1, H2, or H4 (L1.2-H1, L1.2-H2, and L1.2-H4, respectively). Among 32 recombinant human chemokines tested at 100 nM (CC chemokines: CCL1, 2, 3, 4,5,7,8,11,13,14,15,16,17,18,19,20,21,22,24,25,26,27, and 28; CXC chemokines: CXCL4, 8, 9, 10, 12, 13, and 16; XCL1; CX3CL1), CCL16 was found to induce vigorous calcium mobilization in L1.2-H4. Fig.…”
Section: Ccl16 Induces Calcium Mobilization Via H4mentioning
confidence: 99%